Futur anterieur - temps du futur ou temps du passe ? - Ciszewska, Ewa (Neophilologica, 2004)
A future tense future anterieur can be used to describe probability or an event (moment) prior to some other event (moment) in the future, but it may also appear in literary or press texts as a summary of past events. The author focuses her attention on the last usage and analyses the context in order to distinguish these elements which allow the reader to locate a given event on the axis of time. At such occasions future anterieur appears in specific constructions (// aura fallu X temps pour...), and is used with various adverbials of time, with phrases indicating opposition or conclusion as well as with adverbs jamais and rarement.